Strong visible light emission from silicon-oxycarbide nanowire arrays prepared by electron beam lithography and reactive ion etching. Issue 23 (20th November 2015) - Nikas, Vasileios; Tabassum, Natasha; Ford, Brian; Smith, Lloyd; Kaloyeros, Alain E.; Gallis, Spyros
Abstract: Abstract : The present report presents results from the fabrication, structural, and optical characteristics of sub-100 nm thermal chemical vapor deposition-grown silicon-oxycarbide (SiC x O y ) nanowire (NW) arrays fabricated by e-beam lithography and reactive-ion-etching. The composition of SiC x O y materials follows closely the silicon-oxycarbide stoichiometry [SiC x O2(1− x ), (0 < x < 1)] as observed by compositional and structural analysis. The corresponding structural and bonding evolution of SiC x O y are well-correlated with changes in their optical properties, as demonstrated by the linear dependence of their optical gap and refractive index with [Si–C]/[Si–O] bond–area ratio. By virtue of these advantages, properly tailored SiC x O y NWs were fabricated, exhibiting strong room-temperature visible photoluminescence (PL) through engineering of [Si–C]/[Si–O] bonds. The current studies focused on the thermal-oxidation and excitation intensity behavior of SiC x O y NWs revealed their very good stability, as their luminescence characteristics remain unchanged upon annealing in oxygen ambient (250 °C), while the PL intensity dependence on the excitation power-density exhibited a linear increase up to ∼800 W/cm 2 .